2017
DOI: 10.29252/nirp.jpcp.5.4.271
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Personality Characteristics and Early Maladaptive Schema With Suicide Ideation in Iranian Late Adolescents

Abstract: Objective: The aim of this study was to investigate prediction of suicide ideation based on early maladaptive schemas and the Big-Five personality traits in a sample of Iranian late adolescents.Methods: 315 high school students (160 female, 155 male) were recruited by multi-stage cluster sampling method from Shiraz city. Participants completed NEO Five-Factor Inventory, Schema Questionnaire, and Beck Scale for Suicidal Ideation. Data were analyzed using hierarchical regression analysis.Results: showed that ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In a study conducted by Sami et al (2015), the overall reliability of this questionnaire was calculated as 0.83. Valikhani et al (2017) reported the Cronbach α coefficient for each scale as: 0.82 (neuroticism), 0.79 (extroversion), 0.60 (openness to experience), 0.69 (agreement), and 0.75 (conscientiousness). In the present study, Cronbach α for neuroticism, extraversion, and openness to experience, agreement and conscientiousness were computed 0.81, 0.76, 0.79, 0.74 and 0.79, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Sami et al (2015), the overall reliability of this questionnaire was calculated as 0.83. Valikhani et al (2017) reported the Cronbach α coefficient for each scale as: 0.82 (neuroticism), 0.79 (extroversion), 0.60 (openness to experience), 0.69 (agreement), and 0.75 (conscientiousness). In the present study, Cronbach α for neuroticism, extraversion, and openness to experience, agreement and conscientiousness were computed 0.81, 0.76, 0.79, 0.74 and 0.79, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has emphasized the positive contribution of resilience to adjustment in encountering difficult conditions (Theron & Theron, 2013;Werner, 2012;Yates & Grey, 2012). Resilience reduces anxiety and depression (Khadem, Motevalli Haghi, Ranjbari, & Mohammadi, 2017) and individuals with high resilience adjust more successfully to stressors than those with low resilience (Luthar, 2006).…”
Section: Plain Language Summarymentioning
confidence: 99%
“…Interestingly, another cross-sectional online study (Nagra et al, 2016) showed that the presence of dismissing attachments may increase the risk of suicidality in people who self-harm. Similarly, several studies have shown that fearful attachment is associated with suicidal ideation and attempts (Green et al, 2020; Li et al, 2017), and this domain has been found to correlate with suicidal ideation (Valikhani et al, 2017). In other words, disconnection and rejection may be vulnerability factors for suicidality.…”
Section: Discussionmentioning
confidence: 93%